Analysis Of Occupational Safety And Health Risk Factors At Pertamedika Ummi Rosnati Hospital, Banda Aceh, 2026 - Sukardi, Sukardi; Syahrizal, Syahrizal (Jurnal Ragam Pengabdian, 2026)
Occupational Safety and Health (OSH) in hospitals is essential to protect healthcare workers from occupational accidents and work-related diseases. This study aimed to analyze OSH risk factors among nurses in the inpatient wards of Pertamedika Ummi Rosnati Hospital in 2026. A descriptive-analytic design with the Job Hazard Analysis (JHA) approach was used, involving all 23 nurses through total sampling. Data were collected using observation, physical measurements (Sound Level Meter, Lux Meter, and Thermometer), and questionnaires, then analyzed using univariate and Spearman Rank tests. The noise level (68 dB(A)) was below the Threshold Limit Value, while the Asyifa Nurse Station lighting (166.6 lux) did not meet the minimum standard. The Azizah Nurse Station (303.1 lux) and Asyifa Inpatient Ward (340.7 lux) met the lighting standard, whereas the average room temperature (29°C) exceeded the recommended level. Chemical factors were significantly associated with OSH risk (p = 0.048; r = −0.416), while biological, ergonomic, and psychosocial factors were not. Hospitals are recommended to improve chemical exposure control, optimize lighting and room temperature, and strengthen OSH program implementation to reduce occupational risks among nurses.